2018
DOI: 10.1111/jdi.12921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of energy expenditure using doubly labeled water, physical activity by accelerometer and reported dietary intake in Japanese men with type 2 diabetes: A preliminary study

Abstract: The aim of the present study was to determine the total energy expenditure, physical activity and dietary intake of men with type 2 diabetes mellitus and control participants without type 2 diabetes mellitus who were matched for age and body mass index. The participants in the present study were 12 well-controlled type 2 diabetes mellitus patients and 10 controls, aged 40-75 years, with a body mass index <30 kg/m . Total energy expenditure under free-living conditions was assessed using the doubly labeled wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…Since the mean fasting glucose level in the diabetic patients of the present study (127 mg/dL) was much lower than that in the [20] (~ 180 mg/ dL), such an increased basal metabolic rate may not exist in the diabetic patients of the present study. A recent paper using doubly labeled water method reported that energy expenditure in the diabetic patients (mean HbA1c levels, 6.4%) is not different from that in the non-diabetic subjects [22]. This is consistent with the results of the present study that there would be no significant differences in EWL per day between diabetic and non-diabetic subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Since the mean fasting glucose level in the diabetic patients of the present study (127 mg/dL) was much lower than that in the [20] (~ 180 mg/ dL), such an increased basal metabolic rate may not exist in the diabetic patients of the present study. A recent paper using doubly labeled water method reported that energy expenditure in the diabetic patients (mean HbA1c levels, 6.4%) is not different from that in the non-diabetic subjects [22]. This is consistent with the results of the present study that there would be no significant differences in EWL per day between diabetic and non-diabetic subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were shown in the energy and macronutrient intakes. Consequently, when age and body mass index (BMI) are matched, both groups showed no significant difference in TEE and self-reported energy intake [2]. These findings suggest that the significance of providing CR meal on Japanese T2DM patients may be theoretically in doubt [2].…”
mentioning
confidence: 93%
“…However, this figure has been actually estimated to be remarkably lower than the meal intake standards of the Ministry of Health, Labor, and Welfare. diabetic patients [2,3]. Furthermore, several reports were found concerning the efficacy of LCD [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, obese type 2 diabetes patients (BMI ≥30 kg/m 2 ) show higher hedonic hunger analyzed by the power of food scale compared with non‐obese type 2 diabetes patients; there is a positive linear association between hedonic hunger and poor glycemic control in obese type 2 diabetes patients, but not in non‐obese type 2 diabetes patients. Furthermore, self‐reported energy intake does not differ between healthy individuals and type 2 diabetes patients (BMI <30 kg/m 2 ) with relatively good glycemic control (average glucose levels 117 ± 16 and glycated hemoglobin 6.4 ± 0.5%). These results show that eating breakfast and reducing the energy content of evening meals is important for restraining bodyweight gain and hedonic hunger, and maintenance of good glycemic control in type 2 diabetes patients.…”
mentioning
confidence: 96%